Formulation of a Highly Effective Inoculant for Common Bean Based on an Autochthonous Elite Strain of Rhizobium leguminosarum bv. phaseoli, and Genomic-Based Insights Into Its Agronomic Performance - Pastor-Bueis, Raquel; Sánchez-Cañizares, Carmen; James, Euan K.; González-Andrés, Fernando (Frontiers in Microbiology, 2019)
Common bean is a poor symbiotic N-fixer, with a low response to inoculation owing to its promiscuous nodulation with competitive but inefficient resident rhizobia. Consequently, farmers prefer to fertilise them rather than rely on their capacity for Biological Nitrogen Fixation (BNF). However, when rhizobial inoculants are based on autochthonous strains, they often have superior BNF performance in the field due to their genetic adaptations to the local environment. Nevertheless, there is scant information at the genomic level explaining their superiority or on how their genomes may influence the inoculant performance. This information is especially important in technologically advanced agri-systems like Europe, where environmental concerns and increasingly stringent fertiliser regulations are encouraging a return to the use of rhizobial inoculants, but based upon strains that have been thoroughly characterised in terms of their symbiotic performance and their genetics. The aim of this study was to design an inoculant formulation based on a superior autochthonous strain, Rhizobium leguminosarum bv. phaseoli LCS0306, to assess its performance in the field, and to determine the genomic features contributing to the high effectiveness of its symbiosis with common bean. Plants inoculated with the autochthonous strain LCS0306 fixed significantly more nitrogen than those with the allochthonous strains R. phaseoli ATCC 14482T and R. etli CFN42T, and had grain yield similar to the nitrogen-fertilised controls. Inoculation with LCS0306 was particularly efficacious when formulated with a carrier based upon a mixture of perlite and biochar. Whole genome comparisons revealed no differences in the classical symbiotic genes of strain LCS0306 within the symbiovar phaseoli. However, its symbiotic superior performance might be due to its genomic versatility, as it harbours a large assortment of genes contributing to fitness and competitiveness. It is concluded that inoculation with elite rhizobia formulated with perlite-biochar carriers might constitute a step-change in the sustainable cultivation of common bean in Spanish soils.